Improving the Attitudes and Creative Thinking Skills of Senior High School Students Using an ESD-Enhanced STEM Approach - Dhara Fauziyah Aslam; Nur Khoiri; Joko Saefan, Saefan; Ernawati Saptaningrum; Sigit Ristanto (Berkala Ilmiah Pendidikan Fisika, 2024)
The STEM approach is a learning strategy to train students' creative thinking skills. This approach encourages students to conduct the engineering process by making prototypes or products to solve problems. Education for Sustainable Development (ESD) needs to be integrated into STEM learning to train students' thinking and questioning skills. This study aims to determine the improvement of ESD attitudes and creative thinking skills by using the ESD-integrated STEM approach. This study used a one-group pretest-posttest design. The research instruments used were a creative thinking skills test with creative thinking indicators and an ESD attitude questionnaire. The N-Gain test analysis obtained a result of 0.81 with a high category. The results showed that students' creative thinking skills improved significantly, and students' ESD attitudes improved very well through the STEM approach with ESD content in high school students. This research shows that the STEM approach with ESD content can be used as an alternative learning method to improve students' creative thinking skills and can contribute to the development of science by enriching the understanding of the STEM approach with ESD content, presenting a new perspective in education that focuses on sustainability and creativity.